Cost-effectiveness analysis of best management practices for non-point source pollution in watersheds: A review - CHANG Jian; YU Jie; WANG Fei’er; ZHENG Siyuan (浙江大学学报. 农业与生命科学版)
Non-point source (NPS) pollution has been the major influential factor for degradation of water bodies. Best management practices (BMPs), as an integrated system for pollution prevention and control, which combines both structural and non-structural measures, have been considered as one of the most effective solution for non-point source pollution. However, economic cost has been an important factor for screening the best management practice. Taking economic feasibility into consideration, the implementation of BMPs would be more practical and resource- saving, which can effectively alleviate the contradiction between economic development and environmental protection in basin management. Since few studies on research progress of BMPs cost-effectiveness analysis have been reported in China, methods of cost-effectiveness analysis were illustrated in this paper, to provide the foundation for the further research.Recently, relevant researchers have used empirical calculation methods and economic models to estimate costs of BMPs, and non-point source pollution model was developed to evaluate environmental benefits. According to the accounting results, two optimization criteria, namely cost minimization and benefit maximization, were employed to screen for the most cost effective measures. Application of cost-effectiveness analysis method included three categories, coupling NPS model with empirical calculation methods, coupling NPS model with economic model and cost-effectiveness analysis based on optimization algorithm. Besides, the limitations were discussed based on differences of time and space scale in coupling models and uncertainty issues.In the future, as the cost- effectiveness analysis of BMPs is related to various aspects of environmental, economic and social factors, on the one hand, more comprehensive agricultural economic database and water quality database should be built and fully validated, to reduce the uncertainty in the process of simulation. On the other hand, continuous development of computer technology could be expected, to improve efficiency and accuracy of cost-effectiveness analysis, and to strengthen the coupling of different types of model, eventually improving the feasibility in application of cost-effectiveness analysis method.In this paper, three aspects on application of BMPs economical assessment method in non- point source pollution control were illustrated, including concept definition, analysis methods and relevant applications. Suggestions and prospects on trend of further research were also deeply analyzed and summarized.